Un padre no tan padre = From Dad to worse [videorecording (DVD)] - Bonilla, Héctor, 1939-; Bracamontes, Jacqueline, 1979-; Barba, Arturo (Pantelion : Lionsgate, 2017)
After grumpy 85-year-old Don Servando is kicked out of his retirement home, his estranged son Francisco has no choice but to invite his dad to live with him. Confronted with his son's hippie lifestyle and eccentric housemates, Don Servando goes off the rails, igniting a series of comic conflicts that put the house in jeopardy, and leaves everyone in stitches.